Implementación de estrategias metodológicas y didácticas que permitan al docente optimizar el proceso de enseñanza aprendizaje de los estudiantes de preparatoria y segundo año de Básica del Colegio San Antonio de Padua de Pomasqui durante el año lectivo 2016-2017. - Silva Negrete, Dayán Anabel (2018)
The following intervention project systematizes the need posed by high school teachers and second year of the San Antonio de Padua School, who explained the difficulty they had in finding methodological and didactic strategies which would allow them to optimize the teaching-learning process of the school. educational population with which they work. Therefore it was necessary to provide teachers with training on strategies and attention to diversity, for which it was started with a first period based on training workshops aimed at teachers both high school and second year of basic and teacher training. complementary areas of the institution, so that they know, raise awareness and put into practice the approach that educational inclusion has and relate it to the strategies implemented. Subsequently, we proceeded to work with high school teachers and second year of basic so that all the issues addressed in the trainings are put into practice in the teaching-learning process with their students. At the end, the benefits achieved were demonstrated through a comparative analysis of the results of the application of surveys to the students, when initiating and completing the development of the project.